Réponses

Meilleure réponse !
2013-10-14T20:52:59+02:00
Bonsoir, il me semble l'avoir déjà résolue
E = 9x² -15x +5 - (21x² -12x -35x +20)
E = 9x² -15x +5 -21x² +12x +35x -20
E = - 12x² +32x -15
j ai essaye de le faire mais apparemment je me suis trompe encore merci
2013-10-14T21:13:56+02:00

 
 Développement E=9 x^{2} +30x-25+(21 x^{2} -12x-35x+20) =9 x^{2} -30x+25+21 x^{2} -12x-35x+20 =9 x^{2} +21 x^{2} -30x-12x-35x+25+20       E =30 x^{2} -77x-45
 Factorisé E=(3x-5)[(3x-5)+(7x-4)] =(3x-5)(3x-5+7x-4)       E =(3x-5)(10x-9) [/tex]